Statistical Process Control for Debutanizer Column ofPETRONAS Penapisan Terengganu Sdn. Bhd. (PPTSB) - Mahamad @ Muhamad, Zulfadzli (Universiti Teknologi PETRONAS, 2009)
Statistical Process Control (SPC) come up to implement and solving business problems by systematic problem-solving tools. This statistical method is useful in monitoring processes, reducing variability through elimination of assignable causes. In this project, the writer would be doing the Statistical Process Control (SPC) for the debutanizer column. This report will highlight background of the study, problem statement, objectives and scope of study, methodology, results and discussion, conclusion and recommendations for the project. By means of case study, the purpose of this project is to apply statistical process control for debutanizer column of PPTSB. The first section will elaborate on the historical review of monitoring and product quality control for CDU column. Then, the study focus on operation of debutanizer column which the function for this column will elaborate detail.. The discussion on problem statement begins with the objective of using statistical process control for monitoring processes, reducing variability through elimination of assignable causes. Furthermore, this section will elaborate more on the objectives and scope of study for this project. The second section contains the literature review which elaborates on the introduction to Fractionator Column, Debutanizer Column, and Statistical Process Control and benefits of using this tool. The structure of Neural Networks is introduced in this section. The discussion begins with an overview of Neural Network architecture, and how the Neural Network is constructed. The third section discusses the methodology of the project. SPSS software and MICROSOFT EXCEL will be used at all time in order to accomplish the objectives. The latter part covers result and discussion for the Statistical Process Control, which includes data arrangement and graphical analysis. Conclusion part is covered at the end part of this section. lll